2016
DOI: 10.1016/j.cognition.2016.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Object individuation is invariant to attentional diffusion: Changes in the size of the attended region do not interact with object-substitution masking

Abstract: When the human brain is confronted with complex and dynamic visual scenes, two pivotal processes are at play: visual attention (the process of selecting certain aspects of the scene for privileged processing) and object individuation (determining what information belongs to a continuing object over time versus what represents two or more distinct objects). Here we examined whether these processes are independent or whether they interact. Object-substitution masking (OSM) has been used as a tool to examine such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
12
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 36 publications
2
12
0
Order By: Relevance
“…Overall, these results lend support to the idea that visual awareness can be affected independently from selective attention (Goodhew & Edwards, 2016), suggesting that processes following deployment of attention (i.e., object individuation through updating during VWM consolidation) determine whether information is stored in or dropped from memory.…”
Section: Underlying Mechanisms Of Object-substitution Maskingsupporting
confidence: 67%
See 2 more Smart Citations
“…Overall, these results lend support to the idea that visual awareness can be affected independently from selective attention (Goodhew & Edwards, 2016), suggesting that processes following deployment of attention (i.e., object individuation through updating during VWM consolidation) determine whether information is stored in or dropped from memory.…”
Section: Underlying Mechanisms Of Object-substitution Maskingsupporting
confidence: 67%
“…Although we observed a behavioral interaction in the current study (because we did not constrain for ceiling performance), the ERP data suggest that set size influences spatial attention independently from masking. That is to say, OSM disrupts consolidation of the target item independently and at a later time point from the effects of set size on selective attention (also see, Goodhew & Edwards, 2016).…”
Section: Electrophysiological Independence Of Set Size and Maskingmentioning
confidence: 99%
See 1 more Smart Citation
“…Different attentional breadths (global/broad vs. local/narrow), including both those operationalised via Navon stimuli and related paradigms, have been found to have distinct perceptual and cognitive consequences. In particular, a narrow attentional breadth enhances target detection, the spatial resolution of perception, and both feature and conjunction visual search efficiency (Benso, Turatto, & Gastone, 1998; Goodhew & Edwards, 2016; Goodhew, Lawrence, & Edwards, 2017; Goodhew, Shen, & Edwards, 2016; Greenwood & Parasuraman, 1999), whereas a broad attentional breadth enhances processes such as face identity recognition, perception of positive facial expressions, prioritisation of threatening information, ensemble processing, and change detection (Chong & Treisman, 2005; Gao, Flevaris, Robertson, & Bentin, 2011; Macrae & Lewis, 2002; Notebaert, Crombez, Van Damme, Durnez, & Theeuwes, 2013; Pringle, Irwin, Kramer, & Atchley, 2001; Srinivasan & Hanif, 2010).…”
mentioning
confidence: 99%
“…They further reported that younger observers were also vulnerable to OSM under full attention if the target contrast was greatly reduced to simulate age-related declines in contrast sensitivity. An increasing number of subsequent studies showed that the interaction between OSM and attentional manipulation is merely a spurious artifact resulting from the ceiling effect (Argyropoulos, Gelletly, Pilling, & Carter, 2013;Filmer, Mattingley, & Dux, 2014;Goodhew & Edwards, 2016;Pilling, Gellatly, Argyropoulos, & Skarratt, 2014), and that OSM is observed even for fully attended and foveated targets if ceiling performance is carefully avoided (Daar & Wilson, 2016;Filmer, Mattingley, & Dux, 2015). manipulations designed to facilitate the establishment of separate object tokens for the target and mask also attenuate OSM.…”
mentioning
confidence: 99%